Experiences establishing a new speech-language pathology training program in Ethiopia, a resource-limited setting: Lessons learned. - Ganek, Hillary; Ab, Abiye Gebre; Abate, Fikre; Abera, Berhane; Demissie, Hanna; Demissie, Yohannes; Habte, Mesay Gebrehanna; Gravem, Paul Egil; Hakonsen, Hanna; Haye, Alemayehu Teklemariam; Holmefjord, Anders; Mollenhauer, Courtney; et al. (International Journal of Speech-Language Pathology, 2025)
Purpose: Ethiopia is the second most populous country in sub-Saharan Africa. While Ethiopia's health care system includes primary health centres, general, and specialised hospitals, allied health care like speech-language pathology was not available until 2003. This article was written with the aim of sharing the experience of establishing speech-language pathology as a profession and the first speech-language pathology training program in Ethiopia. Method: In this paper, we retrospectively examine how the leadership of local stakeholders, a multidisciplinary team, and the development of a professional infrastructure led to the success of the program. The authorship group, who were involved in the program from inception to implementation, share their experiences. Result: The speech-language pathology undergraduate program at Addis Ababa University graduated its first class in 2019. Plans to grow the training program at the graduate level are ongoing. Conclusion: This novel program, grown from several international partnerships, is an example of how low- and middle-income countries can improve access to the service providers necessary to treat their populations.